Computation analysis of nanofluids in car radiator - Ng, Yen Cheong (2013)
Nanofluids are basically nanoparticles in base fluids. Nanofluids have unique features different from conventional solid-liquid mixtures in which nano sized particles of metals and non-metals are dispersed. Due to enhancement of mechanical properties, nanofluids are widely used in heat transfer industries. Two type of base fluids which are water and 50-50 mixture of Ethylene Glycol with water (EGW) are tested. Copper (Cu) and Alumina (Al2O3) nanoparticles with volume fraction or concentration of 0.5 percent and 5 percent are examined in this study. In the recent decades, car manufacturers are exploring nanotechnology and applying onto mass production car such as Hybrid car that symbolize green products. Nanofluids in car radiator will increase heat transfer of the engine, reducing radiator size hence reducing fuel consumption and higher efficiency. On the other hand, water based nanofluids have better heat transfer compared to EGW based nanofluids. Results also show higher concentration will have better heat transfer. Thermal conductivity of nanoparticles will directly affect the thermal conductivity of the nanofluids and it is proportional related.